2017
DOI: 10.20853/32-1-1575
|View full text |Cite
|
Sign up to set email alerts
|

Study demands, study resources and the role of personality characteristics in predicting the engagement of fist-year university students

Abstract: The objective of this study was to investigate significant predictors of student engagement, including study demands, study resources and personality characteristics. First-year university students (N = 512) participated in the study. The findings showed significant relationships between pace and amount of work and cognitive demands with student engagement, although only cognitive demands was a significant predictor of student engagement in the regression analysis. Even though all the study resources were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 74 publications
1
56
0
Order By: Relevance
“…When the external environment lacks resources, students cannot reduce the potentially harmful influence of SD on MH, leading to an inability to perform ( Kember, 2004 ) adequately. However, resource availability enhances study engagement, strengthening MH ( Cilliers et al, 2018 ). Several studies have shown that specific SR (i.e., peer support, lecturer support, growth opportunities, and information availability) may enhance students’ MH ( Kember, 2004 ; Mokgele and Rothmann, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the external environment lacks resources, students cannot reduce the potentially harmful influence of SD on MH, leading to an inability to perform ( Kember, 2004 ) adequately. However, resource availability enhances study engagement, strengthening MH ( Cilliers et al, 2018 ). Several studies have shown that specific SR (i.e., peer support, lecturer support, growth opportunities, and information availability) may enhance students’ MH ( Kember, 2004 ; Mokgele and Rothmann, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar to employees, students, are faced with various demands. They are expected to attend lectures and seminars, and to invest time in self-studying [ 30 ]. Furthermore, they are demanded to manage high workload, in some disciplines up to 50 hours per week [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perceived and actual workload is frequently associated with workplace burnout [ 2 ]. Further study-related demands arise from the pressure of behaving like a competent professional [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many internal factors can influence learning engagement, including needs, motivation, and personality traits (e.g., learning normative consciousness and learning behaviors; Martin et al, 2016 ; Yamada et al, 2017 ; Cilliers et al, 2018 ). The normative consciousness of learning is an intuitive confidence that students deliberately form in the process of learning.…”
Section: Introductionmentioning
confidence: 99%